Toxoplasmosis in Iran: A guide for general physicians working in the Iranian health network setting: A systematic review - Seyedmohammad Alavi; Leila Alavi (Babol University of Medical Sciences, 2016)
Background: Human toxoplasmosis is an important zoonotic infection worldwide which is caused by the intracellular parasite Toxoplasma gondii (T.gondii). The aim of this study was to review briefly the general aspects of toxoplasma infection in   in Iranian health system network. Methods: We searched published toxoplasmosis related articles in English databases including Science Direct, Pub Med, Scopus, Google Scholar, Magiran, Iran Medex, Iran Doc and Scientific Information Database (SID) for toxoplasmosis. Results: Out of 1267 articles from the English and Persian databases search, 40 articles were suitable with our research objectives and so were selected for the study.  It is estimated that at least a third of the world human population is infected with T.gondii, suggesting it as one of the most common parasitic infections through the world.  Maternal infection during pregnancy may affect dangerous outcome for the fetus, or even cause intrauterine death. Reactivation of a previous infection in immunocompromised patient such as drug induced, AIDS and organ transplantation can cause life-threating central nervous system infection. Ocular toxoplasmosis is one of the most important causes of blindness, especially in individuals with a deficient immune system. Conclusion: According to the increasing burden of toxoplasmosis on human health, the findings of this study highlight the appropriate preventive measures, diagnosis, and management of this disease.